Peran Manajemen Kurikulum Dalam Meningkatkan Mutu Lulusan di SMP Muhammadiyah 1 Kartasura - Nisa, Arum Khairun; Salim, Hakimuddin (Jayapangus Press, 2025)
This study aims to examine the implementation of curriculum management in improving the quality of graduates at SMP Muhammadiyah 1 Kartasura. This study uses a qualitative approach with a case study method to analyze and explain the phenomenon at SMP Muhammadiyah 1 Kartasura. Data were collected through direct observation on site, interviews with informants, and recording school documents. The analysis follows the Miles & Huberman model which combines data collection and analysis. SMP Muhammadiyah 1 Kartasura has a vision of creating quality graduates with broad insight, noble character, and pious. This school has implemented good curriculum management to create graduates who are able to compete with graduates from other schools. The results show that the school implements the K13 curriculum combined with three flagship programs: Tahfidz, IT, and Creative classes. Curriculum management is carried out in a structured manner through planning, organizing, implementing, and evaluating by the school team, including the vice principal for curriculum. The school also runs a religious habituation program and a character approach to shape students with noble character. Several challenges, such as student boredom, delays in memorization programs, and poor student behavior, have been addressed with innovative solutions such as contextual learning, educational punishment systems, and home visit programs. The implementation of sound curriculum management contributes significantly to the achievement of quality graduates, in terms of knowledge, skills, and attitudes.